DEWBoard Clinches Best of the Best Award at CITREX 2025: Innovative Creation Enhancing Teaching Quality of Digital Electronics - Naqiah, Puaad (UMPSA, 2025)
GAMBANG, 23 June 2025 – The research and innovation excellence of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) continues to receive recognition as yet another innovation by one of its lecturers has successfully made history at the Creative, Innovation, Technology and Research Exposition (CITREX) 2025.